Parent–child relationships and psychological distress: survey of parents from low-income families after the COVID-19 pandemic - Wong, Li Ping; Alias, Haridah; Farid, Nik Daliana Nik; Yusop, Sofia Md; Musa, Zuhrah; Hu, Zhijian; Lin, Yulan (Frontiers in Public Health, 2023)
This study aims to shed light on parent–child relationships and the psychological health of parents from low-income families after the easing of the COVID-19 pandemic restrictions. This cross-sectional study recruited 553 parents of children aged 13-24 years in low-income community settings. The Parent-Child Conflict scale of the Parental Environment Questionnaire (PEQ) was used to measure parent–child conflict. Psychological distress was assessed using the Depression, Anxiety, and Stress Scale short form (DASS-21). The study revealed a low level of parent–child conflict in the overall study population, with a median PEQ of 48.0 (interquartile range [IQR] 36 to 48). Concerning demographics, married parents reported a likelihood of having a higher level of parent–child conflict over 3 times higher than single parents (OR = 3.18 95%, CI 1.30–7.75). More parent–child conflicts were also found in parents aged 60–72 years old who were unemployed, retired, or housewives and from lower-income groups. In regard to lifestyle factors, a higher level of physical activity and having enough sleep were associated with lower levels of parent–child conflict. Only approximately 1% of the participants reported symptoms of depression, anxiety, or stress. Low risk exists for parent–child conflict and psychological sequelae following the easing of the COVID-19 pandemic restrictions, which could be due to various support measures implemented by the government. Vulnerable parents identified as being at risk of parent–child conflict warrant attention in future advocacy efforts.